Louise Blanchard Bethune Every Woman Her Own Architect - Hayes McAlonie, Kelly (State University of New York Press, 2023)
As America's first professional female architect, Louise Blanchard Bethune broke barriers in a male-dominated profession that was emerging as a vital force in a rapidly growing nation during the Gilded Age. Yet, Bethune herself is an enigma. Due to scant information about her life and her firm, Bethune, Bethune & Fuchs, scholars have struggled to provide a complete picture of this trailblazer. Using a newly discovered archival source of photographs, architectural drawings, and personal documents, Kelly Hayes McAlonie paints a picture of Bethune never before seen.Born in 1856 in Waterloo and raised in Buffalo, New York, Bethune wanted to be an architect from childhood. In fulfilling her dream, she challenged the nation to reconsider what a woman could do. A bicycle-riding advocate for coeducation, Bethune believed in women's emancipation through equal pay for equal work. This belief would be tested during the design competition for the Woman's Building for the 1893 World's Columbian Exposition, where female entrants were not paid for their work. Bethune refused to participate on principle, but nonetheless her career thrived, culminating in the most important commission of her life, Buffalo's Hotel Lafayette. A comprehensive biography of the first professional woman architect in the United States, who was also the first woman to be admitted to the American Institute of Architects, this book serves as an important addition to New York and architectural history.